Development of a model to predict recurrence after bronchial artery embolization for non-cancer related hemoptysis - Hai-Tao Yan; Guang-Dong Lu; Xiang-Zhong Huang; Da-Zhong Zhang; Kun-Yuan Ge; Jin-Xing Zhang; Jin Liu; Sheng Liu; Hai-Bin Shi; Qing-Quan Zu (BMC Pulmonary Medicine, 2021)
Abstract Background Relapse after effective bronchial arterial embolization (BAE) for controlling hemoptysis is not uncommon. Studies reported diverse predictors of recurrence. However, a model to assess the probability of recurrence in non-cancer related hemoptysis patients after BAE has not been reported. This study was to develop a model to predict recurrence after BAE for non-cancer related hemoptysis. Methods The study cohort included 487 patients who underwent BAE for non-cancer-related hemoptysis between January 2015 and December 2019. We derived the model’s variables from univariate and multivariate Cox regression analyses. The model presented as a nomogram scaled by the proportional regression coefficient of each predictor. Model performance was assessed with respect to discrimination and calibration. Results One-month and 1-, 2-, 3- and 5-year recurrence-free rates were 94.5%, 88.0%, 81.4%, 76.2% and 73.8%, respectively. Risk factors for recurrence were underlying lung diseases and the presence of systemic arterial-pulmonary circulation shunts. This risk prediction model with two risk factors provided good discrimination (area under curve, 0.69; 95% confidence interval, 0.62–0.76), and lower prediction error (integrated Brier score, 0.143). Conclusion The proposed model based on routinely available clinical and imaging features demonstrates good performance for predicting recurrence of non-cancer-related hemoptysis after BAE. The model may assist clinicians in identifying higher-risk patients to improve the long-term efficacy of BAE.